Conceptual Definition of the Term Experimental Architecture: Ambiguity of Terminological Attributions (Prostor, 2022)
Academic literature lacks an unambiguous term to describe architectural and urban planning projects that are borderline feasible, firmly bound to reality but simultaneously also liberated from it, representing an inevitable component of the development of architecture as a discipline. This paper analyses the most commonly used terms in literature, illustrating them with examples and setting forth logical relationships between them as well as the context within which they are positioned. At the same time, the research sets the relationship between Croatian and international experimental architectural practices.